Homomorphic encryption on deep learning in accurate prediction of brain tumour - Sarwar, Arafat; Hossain, Shakhawat; Bhuiyan, Risum Ahmed; Mahmud, Tanun (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.